The sash on the Mersey: the Orange Order in Liverpool, 1819-1982 - Busteed, Mervyn A. (Liverpool University Press, 2025)
Using a wide range of sources including rarely accessed Orange Order records it places the Order within an early nineteenth-century Liverpool context of apocalyptic evangelical Protestantism, a labour market dominated by irregular dock work, a growing influx of immigrant Catholic Irish, marked residential segregation and sporadic civil conflict